Sustainable Innovation Management Model (Mgi) for Plantain Agroindustrial Chain - Gonzalez-Candia, J (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study proposes a sustainable Innovation Management Model (MGI) for the plantain agroindustrial chain, applied to the Quindío region of Colombia. A mixed-methods approach was employed, incorporating various techniques, including a systematic literature review using the Scopus database, which analyzed 95 documents through the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. The identification and prioritization of relevant variables, along with the validation of the proposed model, were also conducted through the use of three questionnaires, supplemented by relevance and congruence indices. The analysis identified 53 variables for the entry stage, 36 for the transformation stage, and 31 for the exit stage. The findings revealed significant gaps within the agroindustrial chain, particularly in areas such as leadership, strategic management, and resilience among key stakeholders. The MGI, as prioritized by stakeholders, provides a framework that integrates variables and information flows, facilitating the development of new open innovation challenges. These challenges engage not only seekers—entities that require innovation—but also solvers—organizations that offer solutions. The implementation of this model will require supportive public policies, projects, and web platforms, such as Innocentive/Wazoku, Ninesigma, Ruta N, Yet2.com, Itonics, and Ennomotive, which, with the aid of artificial intelligence, can connect innovation supply and demand through open challenges. © 2025 by the authors.